Risk of low energy availability, eating disorders and food insecurity amongst development female rugby league players - Sharples, A.; Buchanan, T. D.; Gough, L.; Black, A. D.; Black, K. E. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: There have been several published studies on the prevalence of low energy availability (LEA) risk amongst North American and European endurance athletes. Yet the prevalence and risk factors amongst rugby league players are less well understood. This study assessed the prevalence of low energy availability risk, eating disorder risk, and food security amongst players from a female National Rugby League squad in Australia. METHODS: Players from one Australian professional rugby league club volunteered to participate in the study. An online questionnaire was conducted to determine the prevalence of low energy availability (Low Energy Availability in Females Questionnaire [LEAF-Q]), eating disorder risk (Eating Disorders Inventory [EDI-3]), and food security. RESULTS: Differences between those "at risk" and "not at risk" based on their total LEAF-Q score were determined. Of the 28 players, 64% (N.=18) were at risk of LEA. Raw scores for the EDI-3 subscales, body dissatisfaction (P=0.043), bulimia (P=0.002), composite score (P=0.038), were significantly higher for those at risk and not at risk of LEA. Forty percent of players had some level of food insecurity. CONCLUSIONS: The results suggest LEA risk is similar to other populations and those at risk of LEA are more likely to have an elevated clinical risk of eating disorders. Food security is also an issue in this population and could contribute to LEA risk for some. Future research is needed amongst team sports athletes to understand interplay between eating disorder risk and food insecurity with LEA risk.